Methodological instructions for practical work on the topic «Determination of occupational risks for industrial employees» for the course "Technical and economic analysis of professional and industrial safety" - Movmyga, N. E.; Makarenko, V. V.; Mezentseva, Iryna Oleksandrivna (Національний технічний університет "Харківський політехнічний інститут", 2024)
Any production activity generates certain hazards and risks for workers. The fundamental point of ensuring occupational safety is the risk-oriented approach: development of measures to ensure safe working conditions depending on specific occupational risks at an enterprise. Occupational risk management includes methods to measure and influence the production environment, safety, labour hygiene and health of workers. The scope of management actions in the context of occupational risk covers the selection of priorities, decisions and actions to prevent and eliminate the causes of occupational injuries and health disorders, prevention of accidents, occupational and production-related morbidity. According to DSTU ISO 45001: 2019 "Occupational health and safety management system", the objective of occupational health and safety management is to provide an environment for managing occupational health and safety risks. The expected results of this system are to prevent injuries and harm to employees' health, as well as to ensure safe and healthy working conditions in the workplace. It is important for an organisation to eliminate or reduce occupational health and safety risks through the effective preventive measures.
Keywords: methodical instructions; occupational risks; determination of occupational risks; industrial employees; professional safety; industrial safety